The establishment of Mercosur and the System of Dispute Settlement - Bressan, Regiane Nitsch (Universidade Estadual Paulista / UNESP, 2013)
This study aims to reveal the establishment of Mercosur through the System of Dispute Settlement. The research shows the relations between the institutional solution of trade disputes and the aspects of this system, explaining the procedures and instruments of this mechanism, which contributes to establish the Mercosur. In addition, it provides an understanding about the process which reformed the System. Although it resulted in the Protocol of Olivos, differences are still denoted such as the countries’ views about the establishment of the system. While Uruguay was defending the system as a legal strength, Brazil was reluctant, supporting the maintenance of procedures that would allow extensive negotiations by diplomatic and political ways. Therefore, some desired changes, like eliminating the step of intervention by the Common Market Group and also the access of individuals have not been accomplished. On the other hand, the creation of the Permanent Court of Review by the Protocol of Olivos was the largest institutional innovation to this System. However, its success depends on the willingness of the countries to use this Court and obey its decisions. Thus, this article clearly demonstrates that the preference of Brazil and Argentina for political negotiations affect the success of this institutional structure of Mercosur.